2013
DOI: 10.1177/1073858413494269
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal and Ventral Attention Systems

Abstract: The idea of two separate attention networks in the human brain for the voluntary deployment of attention and the reorientation to unexpected events, respectively, has inspired an enormous amount of research over the past years. In this review, we will reconcile these theoretical ideas on the dorsal and ventral attentional system with recent empirical findings from human neuroimaging experiments and studies in stroke patients. We will highlight how novel methods—such as the analysis of effective connectivity or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
533
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,099 publications
(634 citation statements)
references
References 63 publications
40
533
1
2
Order By: Relevance
“…They suggested that such activations express reflexive attention to salient, incongruent or infrequent stimuli; in other words, stimuli that are relatively distinct, triggering memory-enhancing processes that have more impact on immediate memory. Because we used an immediate memory test here, we expected to confirm their hypothesis, and predicted that in mixed lists we would observe greater subsequent memory effects in regions belonging to the ventral attention network ( VAN) for emotional compared to neutral stimuli (Corbetta, Patel, & Shulman, 2008;Viviani, 2013;Vossel, Geng, & Fink, 2014).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…They suggested that such activations express reflexive attention to salient, incongruent or infrequent stimuli; in other words, stimuli that are relatively distinct, triggering memory-enhancing processes that have more impact on immediate memory. Because we used an immediate memory test here, we expected to confirm their hypothesis, and predicted that in mixed lists we would observe greater subsequent memory effects in regions belonging to the ventral attention network ( VAN) for emotional compared to neutral stimuli (Corbetta, Patel, & Shulman, 2008;Viviani, 2013;Vossel, Geng, & Fink, 2014).…”
Section: Introductionmentioning
confidence: 85%
“…the contrast [-1 1 1 -1. In the dorsal attention network (Corbetta et al, 2008;Fox, Corbetta, Snyder, Vincent, & Raichle, 2006;Uncapher & Wagner, 2009) (Corbetta et al, 2008), and sometimes considered a mediator between attentional networks (Vossel et al, 2014). In addition we identified significant activations in memory / visual areas in right lingual gyrus (peak xyz = 24, -68, -2; Z = 4.87; KE = 1710; peak p < .001) extending into fusiform gyrus (peak xyz = 24, -74, -8) and parahippocampal gyrus (peak xyz = 24, -50, -8).…”
Section: Figure 2 Ventral Activation Identified In Two Way Interactimentioning
confidence: 99%
“…The greater decreased activation predominantly in the cortical regions in our HIV participants also indicate lesser requirement of the “top‐down” attention network 24. In contrast, SN controls showed improved “bottom‐up” networks after adaptive WMT, suggesting that the processing might have become more automated 45. However, the decreased brain activation after adaptive WMT in our participants contrasts with the increased striatal BOLD signals following adaptive WMT in healthy individuals46 and in children with ADHD 47.…”
Section: Discussionmentioning
confidence: 54%
“…The brain's functionally and structurally independent yet cooperative attention network [98], is a fundamental component of our ability to selectively direct the brain's limited processing resources to the information of most relevance within the environment, which in turn influences many other aspects and levels of processing including cognition and perception. Research evidence indicates that some aspects of attention-related function can be influenced and modulated by anxiety [12,47,[99][100][101].…”
Section: Anxiety and Attention-related Processingmentioning
confidence: 99%